Kajian Kepuasan Pelanggan Air Minum (PDAM) Dengan Menggunakan Konsep Service Quality (SERVQUAL) Di Komplek Perumahan Kota Solok - Ferya Askal; Melinda Noer; Denny Helard (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
This study aims to measure the level of user satisfaction of PDAM Solok City drinking water services and measure the variables that significantly affect customer satisfaction on the quality of service by PDAM in the provision of drinking water in the housing complex of Solok City. This study used a quantitative and inferential descriptive statistical analysis approach, the data was analyzed inferentially with the Structural Equation Model/SEM. Based on the results of the research that has been done, it was found that the research respondents answered that they were satisfied with the drinking water service of PDAM Kota Solok, then based on the results of data processing using SmartPLS, the dimensions of empathy and assurance play a significant role in influencing the level of customer satisfaction. Both of these aspects must be considered by company management so that service performance can be continuously improved